The metabolic syndrome in healthy, multiethnic adolescents in Toronto, Ontario: The use of fasting blood glucose as a simple indicator - Vuksan, Vladimir (Pulsus Group Inc, 2010)
BACKGROUND: The prevalence of the metabolic syndrome (MetS) is increasing worldwide and prevention represents a major challenge. Usually identified in middle age, the MetS has pediatric roots and there are variable incidence rates between ethnic groups. Due to the difficulty of diagnosis, it remains largely undetected in adolescents. OBJECTIVES: To assess the presence of the MetS features in healthy, normal-weight, multiethnic adolescents and to determine whether fasting blood glucose (FBG) could function as a simple indicator of its presence. METHODS: A convenience sample of secondary school students was used in a cross-sectional study. General linear model ANCOVA adjusted for multiple pairwise comparisons by the post hoc Tukey-Kramer test was used to assess differences among the tertiles of FBG. RESULTS: A total of 182 adolescents from 62 Greater Toronto Area secondary schools in Ontario were recruited (44% Caucasian, 34% South Asian and 22% Chinese), with a mean (± SD) age of 17.4±0.9 years, a mean body mass index of 22.1±3.4 kg/m(2) and a mean FBG of 4.92±0.4 mmol/L. Analysis with general linear model ANCOVA across the tertiles of FBG (3.83 mmol/L to 4.78 mmol/L, 4.79 mmol/L to 5.08 mmol/L, and 5.09 mmol/L to 6.45 mmol/L) showed significant linear increases of body mass index (P<0.005), waist circumference (P<0.001), systolic blood pressure (P<0.001) and diastolic blood pressure (P<0.05) with increasing FBG. Stepwise multiple regression analysis indicated systolic blood pressure (beta=0.0078, partial R(2)=0.039, P=0.007) and waist circumference (beta=0.0081, partial R(2)=0.025, P=0.035) were independent predictors of the increased FBG level. CONCLUSIONS: MetS markers were present in a sample of healthy multiethnic adolescents in the Greater Toronto Area. FBG could be used as a simple indicator of the MetS to allow for early detection of the presence of the MetS and the introduction of preventive lifestyle measures. Further studies with larger sample sizes should address the accuracy of FBG for diagnosing the MetS.